KONSELING LINTAS AGAMA DAN BUDAYA DALAM FENOMENA HIJRAH DAN PERILAKU BERAGAMA MILENIAL DI MEDIA SOSIAL (Kajian Pada Fenomena Pamer Kebaikan di Media Sosial) - Ana Bella Puandina; Sekar Ayu Aryani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This research is motivated by the phenomenon of migration which has recently been happening to millennials on social media, which has made changes to the religious behavior of the millennials themselves. Millennials tend to show off their religious activities on social media which should be part of private rather than public affairs. But now, social media has given birth to a new culture where religious behavior is no longer a personal matter between humans and their God, but is also part of the activities that are usually displayed in the media display space, especially social media. The migration trend carried out by millennials brings new changes to religious behavior on social media, someone can easily be called someone who is devoutly religious just by sharing posts about religion, and sharing alms by uploading them on social media. The purpose of this study is to find out that the phenomenon of migration and religious behavior that likes to show off the goodness and piety of millennials on social media is overcome by providing cross-religious and cultural counseling. The research method used is library research or library research with a qualitative type. The results of the study show that cross-religious and cultural counseling is deemed capable of dealing with the trend of showing off kindness and piety on social media.